Health divide : economic and demographic factors associated with self-reported health among older Malaysians. - Haron, Sharifah Azizah; Sharpe, Deanna L.; Masud, Jariah; Abdel-Ghany, Mohamed (Springer Verlag, 2010)
Data from the 2004 Survey of Economic and Financial Aspects of Aging in Malaysia were analyzed to determine factors associated with self-reported health status among older Malaysians. Odds of self-reporting health as bad versus moderate or good were higher for respondents who were in lower income quintiles, who perceived their financial situation as bad, who were older and who were not married. Malay, Chinese, Indian, and Bumiputra ethnic groups had lower odds of perceiving their health to be bad as compared with those in other ethnic groups.